Black sands [large type] - Coble, Colleen (Coble, Colleen. Aloha Reef series, 2008)
When Annie Tagama's beautiful sister Leilani disappears and her necklace is found near an active volcano, Annie is sure something has happened to her. About the same time, Mano Ohana, the man she blames for her brother's death, shows up with news that her brother had a bank account containing over two million dollars and that he might not be dead, after all. How this ties into Leilani's disappearance, if it does, is something that Mano is determined to discover; and as he and Annie get closer to the truth--and each other--they also get closer to a danger that threatens the whole island as well as their families.